A full-flexible triazine-based covalent organic framework material and a preparation method and application thereof
Patent Information
- Application Number
- CN202611406743.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-13
AI Technical Summary
然而此现有技术仍存在以下不足:(1)该COFs的分子骨架为刚性结构,螯合位点数量有限,对铀酰离子的吸附容量仍有提升空间;(2)该材料仅具备吸附功能,缺乏光催化还原性能,难以实现铀的深度去除
(1)本发明的全柔性三嗪基COFs材料的平衡吸附量为1808mg/g。本发明以2,3-二羟基丁二酸二酰肼作为共缩聚单体,在保持三嗪环骨架和“亚胺-羟基”螯合位点的同时,引入了柔性脂肪链段(—CH(OH)—CH(OH)—),该柔性链段的引入带来两方面的显著优势:其一,柔性链段赋予COFs骨架一定的构象自由度,能够使骨架中的螯合位点发生适度构象调整,从而更充分地暴露并与铀酰离子配位,相当于在刚性骨架的基础上增加了有效的铀酰离子结合位点密度;其二,柔性链段中的邻二羟基结构本身可作为额外的铀酰离子螯合位点,与亚胺基团和酚羟基形成协同配位效应,进一步增强了材料对铀酰离子的亲合度和吸附容量。
Smart Images

Figure CN122897958A_ABST
Abstract
Description
Technical Field
[0001] This invention discloses a fully flexible triazine-based covalent organic framework material, its preparation method, and its application, belonging to the field of nanomaterial preparation technology for uranium extraction from seawater. Background Technology
[0002] Uranium is a key element in the nuclear industry, and ensuring sufficient uranium resources is an important foundation for the development of nuclear energy by all countries in the world. With the increasing global demand for nuclear energy, the scale and number of nuclear power plants will continue to increase, leading to a greater demand for uranium resources. Therefore, finding exploitable and economically viable uranium resources is urgently needed to ensure the sustainable development of the nuclear industry.
[0003] The total uranium resources in seawater are approximately 4.5 billion tons, a thousand times the reserves of uranium deposits on land. Therefore, extracting uranium from the environment is beneficial to the sustainable development of the energy industry. Furthermore, the process of extracting uranium from seawater is very environmentally friendly, causing no damage and enabling coordinated development of resource extraction and environmental protection—a green and environmentally friendly uranium mining technology. However, the uranium concentration in seawater is very low, approximately 3.3 ppb, and numerous interfering ions exist, making uranium extraction from seawater challenging. Moreover, the presence of a wide variety of microorganisms in seawater further complicates the process through their attachment and metabolism. Currently, the main methods for seawater uranium extraction include membrane separation, ion exchange, solution extraction, and chemical precipitation. While these methods are effective for specific systems, their general applicability is limited. Compared to these methods, adsorption separation is simple to operate, low in cost, highly efficient, and widely applicable, making it a highly promising separation method.
[0004] Covalent organic frameworks (COFs) possess advantages such as large specific surface area, high crystallinity, regular porosity, and tunable functional groups, making them ideal materials for uranium capture in seawater. While numerous reports exist on uranium adsorbents based on COFs, most existing COFs are in powder form, which is inconvenient for practical applications and results in low recovery rates. Furthermore, due to the high salinity, diverse metal ion composition, and extremely low uranyl ion concentration of seawater, the adsorption effect of existing COFs on uranium remains unsatisfactory.
[0005] The prior art disclosed in CN117209698A is a triazine-based covalent organic framework material, its preparation method and application. This organic framework material has strong acid and alkali resistance, strong anti-interference ability and specific adsorption capacity for uranyl ions. However, this prior art still has the following shortcomings: (1) The molecular skeleton of this COFs is a rigid structure with a limited number of chelation sites, and there is still room for improvement in the adsorption capacity for uranyl ions; (2) This material only has adsorption function and lacks photocatalytic reduction performance, making it difficult to achieve deep removal of uranium.
[0006] In summary, existing COFs materials still suffer from technical problems such as limited adsorption sites, insufficient adsorption capacity, and lack of photocatalytic reduction synergy. There is an urgent need to develop a new type of COFs material that combines high adsorption capacity and photocatalytic reduction capability. Summary of the Invention
[0007] To address the aforementioned problems in the prior art, this invention provides a fully flexible triazine-based covalent organic framework material, its preparation method, and its applications.
[0008] One objective of this invention is to provide a fully flexible triazine-based covalent organic framework material, wherein the organic framework material has the following structure: .
[0009] The second objective of this invention is to provide a method for preparing a fully flexible triazine-based covalent organic framework material, the method comprising the following steps: Step 1: Mix 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine, 2,3-dihydroxysuccinic acid dihydrazide, solvent and catalyst, and then sonicate to obtain a mixed solution; Step 2: After degassing the mixed solution, seal it and heat it to react. After the reaction is completed, wash, Soxhlet extract and dry it in sequence to obtain a fully flexible triazine-based covalent organic framework material.
[0010] Preferably, in step 1, the molar ratio of 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine and 2,3-dihydroxysuccinic acid dihydrazide is 1:(1~3.5).
[0011] Preferably, the solvent in step 1 is a combination of one of o-dichlorobenzene or mesitylene and one of 1-butanol or 1,4-dioxane.
[0012] Preferably, the catalyst in step 1 is an aqueous solution of acetic acid with a concentration of 5-7 mol / L.
[0013] Preferably, the volume ratio of solvent to catalyst in step 1 is (5~15):1.
[0014] Preferably, in step 1, the ratio of the total mass of 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine and 2,3-dihydroxysuccinic acid dihydrazide to the solvent is (55~105) mg: (1~5) mL.
[0015] Preferably, the heating temperature in step 2 is 80~150℃, and the reaction time is 3~7 days.
[0016] The third objective of this invention is to provide an application of the above-mentioned fully flexible triazine-based covalent organic framework material as an adsorbent in seawater uranium extraction.
[0017] Preferably, the amount of adsorbent added is 0.1~1g / L.
[0018] The fourth objective of this invention is to provide an application of the above-mentioned fully flexible triazine-based covalent organic framework material as one of the raw materials in the preparation of membrane materials.
[0019] The fifth objective of this invention is to provide an application of a membrane material comprising the above-mentioned fully flexible triazine-based covalent organic framework material in seawater uranium extraction.
[0020] The beneficial effects of this invention are as follows: (1) The equilibrium adsorption capacity of the fully flexible triazine-based COFs material of the present invention is 1808 mg / g. The present invention uses 2,3-dihydroxysuccinic acid dihydrazide as a co-condensation monomer. While maintaining the triazine ring skeleton and the "imine-hydroxyl" chelating site, a flexible aliphatic segment (—CH(OH)—CH(OH)—) is introduced. The introduction of this flexible segment brings two significant advantages: First, the flexible segment gives the COFs skeleton a certain degree of conformational freedom, which allows the chelating sites in the skeleton to undergo appropriate conformational adjustments, thereby exposing them more fully and coordinating with uranyl ions. This is equivalent to increasing the effective density of uranyl ion binding sites on the basis of the rigid skeleton. Second, the ortho-dihydroxy structure in the flexible segment can itself serve as an additional uranyl ion chelating site, forming a synergistic coordination effect with the imine group and phenolic hydroxyl group, further enhancing the affinity and adsorption capacity of the material for uranyl ions.
[0021] (2) The fully flexible triazine-based covalent organic framework material of the present invention also possesses photocatalytic reduction properties, achieving a uranium removal rate of 99.3% under illumination. The introduction of flexible segments modulates the overall electron cloud density and band structure of the covalent organic framework, giving the material a suitable band gap and photoresponse capability. Under illumination, the material can generate photogenerated electron-hole pairs, where the photogenerated electrons can remove soluble hexavalent uranyl ions (UO2) adsorbed on the material surface. 2+ ) is reduced to insoluble tetravalent uranium ions (U 4+ The uranium is deposited on the material surface or within the pores in the form of UO2 or U3O8, thereby achieving efficient removal of uranium from the liquid phase to the solid phase. This synergistic mechanism of "adsorption-photocatalytic reduction" enables the material of this invention to achieve a uranium removal rate of over 99% in complex environments such as natural seawater, which is significantly better than that of single adsorption materials.
[0022] (3) The raw materials required for this invention are widely available and have low cost.
[0023] (4) The fully flexible triazine-based covalent organic framework material prepared by the present invention has high stability. After multiple cycles of use, the uranium removal rate can still reach more than 90%. Attached Figure Description
[0024] Figure 1 This is a schematic diagram illustrating the synthesis mechanism of the fully flexible triazine-based covalent organic framework material of the present invention; Figure 2 The infrared spectrum of the fully flexible triazine-based covalent organic framework material of this invention; Figure 3 This is a solid-state carbon NMR spectrum of the fully flexible triazine-based covalent organic framework material of this invention. Figure 4 The N2 adsorption-desorption curves of the fully flexible triazine-based covalent organic framework material of this invention are shown. Figure 5 This is the adsorption isotherm of the fully flexible triazine-based covalent organic framework material of this invention; Figure 6 The photocatalytic synergistic adsorption curves of the fully flexible triazine-based covalent organic framework material of this invention are shown. Figure 7 This is a graph showing the number of times the fully flexible triazine-based covalent organic framework material of this invention is recycled and reused, along with its adsorption effect. Figure 8 This is a BET pore size distribution diagram of the fully flexible triazine-based covalent organic framework material of the present invention. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the present invention clearer, the embodiments of the present invention will be described in further detail below. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0026] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.
[0027] Example 1 The preparation method of the fully flexible triazine-based covalent organic framework material in this embodiment is carried out according to the following steps (synthesis mechanism as follows) Figure 1 (as shown) 0.1 mmol of 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine, 0.15 mmol of 2,3-dihydroxysuccinic acid dihydrazide, 1.5 mL of o-dichlorobenzene, and 1.5 mL of 1,4-dioxane were placed in a 15 mL ampoule, and 0.2 mL of acetic acid aqueous solution (7 mol / L) was added. The mixture was sonicated for 5 min to ensure homogeneity. Then, the mixture was degassed by a three-stage freeze-vacuum-thaw cycle and flame-sealed at 120 °C for 3 days. After the reaction, the product was washed with dichloromethane and tetrahydrofuran three times each. The product was then subjected to Soxhlet extraction with dichloromethane and tetrahydrofuran for one day each. Finally, the product was vacuum-dried at 60 °C for 12 hours to obtain the fully flexible triazine-based COFs material.
[0028] The fully flexible triazine-based COFs material obtained in this embodiment was characterized in a series of ways: (a) The fully flexible triazine-based COFs material obtained in Example 1 was characterized by infrared spectroscopy, and the results are as follows: Figure 2 As shown. From Figure 2 It can be seen that at 1628 cm -1 The presence of a stretching vibration absorption peak at the C=N bond indicates that the fully flexible triazine-based COFs material has been successfully synthesized.
[0029] (ii) Solid-state nuclear magnetic resonance carbon spectroscopy (CMR) 13 The fully flexible triazine-based COFs material obtained in this embodiment was characterized by CCP / MAS SS-NMR, and the results are as follows: Figure 3 As shown. From Figure 3 It can be seen that a characteristic signal peak of triazine ring carbon atoms appeared at about 173 ppm, and a characteristic signal peak of imine bond (C=N) carbon atoms appeared at about 150-160 ppm, further confirming that the fully flexible triazine-based COFs material of the present invention was successfully synthesized.
[0030] (III) The specific surface area and porosity of the fully flexible triazine-based COFs material were determined using N2 adsorption-desorption isotherms. The N2 adsorption-desorption curves are shown below. Figure 4 As shown, the Brunauer-Emmett-Teller (BET) has a specific surface area of 1,023.71 m². 2 / g, BET pore size distribution data as follows Figure 8 As shown, the pore size is about 1.2 nm, indicating that the material has a large specific surface area and a regular mesoporous structure, which is conducive to the diffusion and adsorption of uranyl ions.
[0031] Example 2 The preparation method of the fully flexible triazine-based covalent organic framework material in this embodiment is carried out according to the following steps: 0.1 mmol of 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine, 0.1 mmol of 2,3-dihydroxysuccinic acid dihydrazide, 0.5 mL of o-dichlorobenzene, and 0.5 mL of 1,4-dioxane were placed in a 15 mL ampoule, and 0.2 mL of acetic acid aqueous solution (6 mol / L) was added. The mixture was sonicated for 5 min to ensure homogeneity. Then, the mixture was degassed by a three-stage freeze-vacuum-thaw cycle and flame-sealed at 150 °C for 3 days. After the reaction, the product was washed with dichloromethane and tetrahydrofuran three times each. The product was then subjected to Soxhlet extraction with dichloromethane and tetrahydrofuran for one day each. Finally, the product was vacuum-dried at 60 °C for 12 hours to obtain the fully flexible triazine-based COFs material.
[0032] Example 3 The preparation method of the fully flexible triazine-based covalent organic framework material in this embodiment is carried out according to the following steps: 0.1 mmol of 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine, 0.35 mmol of 2,3-dihydroxysuccinic acid dihydrazide, 2 mL of mesitylene, and 3 mL of 1-butanol were placed in a 15 mL ampoule, and 0.5 mL of acetic acid aqueous solution (5 mol / L) was added. The mixture was sonicated for 5 min to ensure homogeneity. Then, the mixture was degassed by a three-stage freeze-vacuum-thaw cycle and flame-sealed at 80 °C for 7 days. After the reaction, the product was washed with dichloromethane and tetrahydrofuran three times each. The product was then subjected to Soxhlet extraction with dichloromethane and tetrahydrofuran for one day each. Finally, the product was vacuum-dried at 60 °C for 12 hours to obtain the fully flexible triazine-based COFs material.
[0033] Example 4: Application of fully flexible triazine-based covalent organic framework materials in seawater uranium extraction The application of fully flexible triazine-based COFs materials in seawater uranium extraction is as follows: (1) Seawater treatment. Seawater samples taken from the Bohai Sea (Binzhou section, Shandong) were filtered through a 0.22μm water system membrane to remove insoluble substances (such as particulate matter). The uranium concentration range of the spiked seawater was 1-2000ppm.
[0034] (2) Seawater adsorption experiment 1: 10 mL of seawater was placed in a centrifuge tube, and 5 mg of adsorbent (the fully flexible triazine-based COFs material obtained in Example 1) was added. The tube was shaken in a constant temperature shaker at 25 °C for 24 h until adsorption equilibrium was reached. After standing for a while, the adsorbed solution was filtered through a 0.22 μm aqueous system filter membrane. The remaining uranium content was then analyzed by ICP-MS, and the equilibrium adsorption amount was calculated. The results are as follows: Figure 5 As shown, the equilibrium adsorption capacity of the fully flexible triazine-based COFs material is 1808 mg / g.
[0035] (3) Seawater adsorption experiment 2: 10 mL of seawater was placed in a centrifuge tube, and 5 mg of adsorbent (the fully flexible triazine-based COFs material obtained in Example 1) was added. The mixture was shaken in a constant temperature shaker at 25 °C for 24 h until adsorption equilibrium was reached. After standing for a while, the adsorbed solution was filtered through a 0.22 μm aqueous system filter membrane. The remaining uranium content was then analyzed by ICP-MS to calculate the uranium removal rate. After adsorption, the fully flexible triazine-based COFs material was removed and desorbed using 0.1 M nitric acid solution to wash away the uranium. After washing, the seawater adsorption experiment was repeated, for a total of 5 tests. The test results are as follows: Figure 7 As shown, the results indicate that after five recycling cycles, the uranium removal rate of the fully flexible triazine-based COFs material is still greater than 90%.
[0036] (4) Seawater adsorption experiment 3: Seawater adsorption experiments were conducted under illumination. Samples were taken at intervals starting from the 0-minute illumination time, and the percentage of remaining uranium in the seawater was analyzed using ICP-MS. The analysis results are as follows: Figure 6 As shown, the results indicate that under illumination, after 330 minutes of adsorption, the remaining uranium content was 0.7%, meaning the uranium removal rate reached 99.3%.
[0037] Comparative Example 1 This comparative example prepared rigid triazine-based COFs material (COF-DDTT) according to the method of Example 1 in the prior art published in CN117209698A. Specifically, in the preparation process, 2,5-dihydroxy-1,4-benzenedicarboxaldehyde was used to replace 2,3-dihydroxysuccinic acid dihydrazide in this invention with an equimolar amount, and the remaining steps were the same as in Example 1. Seawater uranium extraction performance was tested under the same conditions, and the results showed that the equilibrium adsorption capacity of COF-DDTT was 1720 mg / g. Furthermore, under light irradiation, the conversion of hexavalent uranium to tetravalent uranium could not be achieved, failing to reach the removal rate level of the fully flexible triazine-based COFs material of this invention under the synergistic effect of "adsorption + photocatalysis".
[0038] Comparative Example 2 The preparation method of the COFs material in this comparative example is basically the same as that in Example 1, except that an equimolar amount of succinic acid dihydrazide is used to replace 2,3-dihydroxysuccinic acid dihydrazide (lacking the ortho-dihydroxy structure) during the preparation process. The remaining steps are the same as in Example 1. Under the same conditions, the seawater uranium extraction performance was tested. The equilibrium adsorption capacity of the COFs material obtained in this comparative example was only 1423 mg / g, significantly lower than the 1808 mg / g of the fully flexible triazine-based COFs material of this invention. This indicates that the ortho-dihydroxy structure, as an additional chelating site, plays an important role in improving the uranium adsorption capacity.
Claims
1. A fully flexible triazine-based covalent organic framework material, characterized in that, It has the following structure: 。 2. A method for preparing a fully flexible triazine-based covalent organic framework material, characterized in that, Follow these steps: Step 1: Mix 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine, 2,3-dihydroxysuccinic acid dihydrazide, solvent and catalyst, and then sonicate to obtain a mixed solution; Step 2: After degassing the mixed solution, seal it and heat it to react. After the reaction is completed, wash, Soxhlet extract and dry to obtain a fully flexible triazine-based covalent organic framework material.
3. The method according to claim 2, characterized in that, In step 1, the molar ratio of 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine and 2,3-dihydroxysuccinic acid dihydrazide is 1:(1~3.5).
4. The method according to claim 2, characterized in that, In step 1, the solvent is a combination of one of o-dichlorobenzene or mesitylene and one of 1-butanol or 1,4-dioxane, and the catalyst is an aqueous solution of acetic acid with a concentration of 5-7 mol / L.
5. The method according to claim 2, characterized in that, In step 1, the volume ratio of solvent to catalyst is (5~15):
1.
6. The method according to claim 2, characterized in that, In step 1, the ratio of the total mass of 2,4,6-tris(4-aminophenoxy)-1,3,5-triazine and 2,3-dihydroxysuccinic acid dihydrazide to the solvent is (55~105) mg: (1~5) mL.
7. The method according to claim 2, characterized in that, In step 2, the temperature for heating the reaction is 80~150℃, and the reaction time is 3~7 days.
8. An application of the fully flexible triazine-based covalent organic framework material according to claim 1, characterized in that, The organic framework material is used as an adsorbent or photocatalyst for uranium extraction from seawater or uranium-containing wastewater.
9. An application of the fully flexible triazine-based covalent organic framework material according to claim 1, characterized in that, The organic framework material is used as one of the raw materials in the production of membrane materials.
10. The application of the fully flexible triazine-based covalent organic framework material according to claim 9, characterized in that, The membrane material is used to extract uranium from seawater or uranium-containing wastewater.
Citation Information
Patent Citations
Triazinyl covalent organic framework material as well as preparation method and application thereof
CN117209698A